2013
DOI: 10.2337/db13-0299
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Intestinal and Hepatic Activities of FXR and LXRα Supports Metabolic Effects of Terminal Ileum Interposition in Rodents

Abstract: The farnesoid X receptor (FXR) and the liver x receptors (LXRs) are bile acid–activated receptors that are highly expressed in the enterohepatic tissues. The mechanisms that support the beneficial effects of bariatric surgery are only partially defined. We have investigated the effects of ileal interposition (IT), a surgical relocation of the distal ileum into the proximal jejunum, on FXR and LXRs in rats. Seven months after surgery, blood concentrations of total bile acids, taurocholic acid, an FXR ligand, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 51 publications
(61 reference statements)
0
37
0
Order By: Relevance
“…The tune page parameters were automatically optimized injecting taurocholic acid at 1 μM as standard. The MS/MS detection was operated in MRM mode using a collision energy of 20 (arbitrary units) and the observed transitions are reported in Mencarelli et al, 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tune page parameters were automatically optimized injecting taurocholic acid at 1 μM as standard. The MS/MS detection was operated in MRM mode using a collision energy of 20 (arbitrary units) and the observed transitions are reported in Mencarelli et al, 2013.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, FXR plays a crucial beneficial role in triglyceride and cholesterol homeostasis, as well as in glucose metabolism (Fiorucci et al, 2004, 2007, 2009, 2010a,c; Cariou et al, 2006; Zhang et al, 2006; Cipriani et al, 2010; Mencarelli et al, 2013; Swanson et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…34 After centrifugation at 16000g for 10 min, the clear supernatant was transferred to a new vial, snap frozen, and lyophilized. The samples were then redissolved in methanol−water (2:1, v/v) for tauroconjugated bile acids determination.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…In a seminal study, Dr. Koopmans demonstrated that transposition of 5, 10, or 20 cm of the ileum to the duodenum produced a lengthdependent reduction in food intake and body weight, with the effects more robust in rats made obese with lesions in the ventromedial hypothalamus . Others studies in rats have since reported that IT surgery either produces a significant reduction in intake and weight gain (Atkinson et al 1982;Boozer et al 1990;Chen et al 1990;Chelikani et al 2010;Grueneberger et al 2013;Koopmans et al , 1984Ramzy et al 2014;Strader et al 2005;Wang et al 2008), or no effect on these parameters (Cummings et al 2010;Patriti et al 2007;Mencarelli et al 2013). These inconsistencies are likely due to varying lengths of transposed ileal segments and animal models.…”
Section: Ileal Transposition Surgery: Effects On Energy Balancementioning
confidence: 99%